Gruber's complete PSAT/NMSQT guide 2014 - Gruber, Gary R. (Naperville, Ill. : Sourcebooks Edu, 2013)
A guide to preparing for the Preliminary SAT/National Merit Scholarship Qualifying Test (PSAT/NMSQT) providing test-taking strategies, subject reviews and quizzes, and three practice PSAT tests with explained answers.
Young Adult.
Young Adult
Keywords: National Merit Scholarship Qualifying Test -- Study guides; PSAT (Educational test) -- Study guides; National Merit Scholarship Qualifying Test -- Study guides; PSAT (Educational test) -- Study guides